Leisure and the Internet: Mood states of the elderly during their first Internet contact - Schwartz, Gisele Maria [UNESP]; Campagna, Jossett [UNESP]; Pereira Santiago, Danilo Roberto [UNESP]; Filho, Sandro Carnicelli [UNESP]; Da Costa Teixeira, Heraldo Marconi [UNESP]; Abrucez, Paula Manco [UNESP]; Christofoletti, Danielle Ferreira Auriemo [UNESP] (Taylor & Francis, 2010)
It seems clear that in developing countries, personal and social barriers affect equal opportunities for accessing new technologies in the leisure area, especially when focusing on the elderly. The purpose of this study was to identify changes in mood states among a sample of elderly people during their first leisure time Internet access. The LEA-RI (Revised and Illustrated Mood State List) instrument and a survey were used to gather before-and-after data from a purposive sample of 100 elderly of both sexes who were participants in a program introducing leisure time computer use to the elderly in Rio Claro, Brazil. The results showed that before initiating access, a mood state of fear was indicated by 91 per cent of participants, agitation and nervousness by 7 per cent, and timidity by 3 per cent. Following the session, these unpleasant feelings were replaced, in the case of 85 per cent of participants, by positive mood states like light, active and happy. Overcoming the challenge improved self-esteem and feelings of joy. In the case of 15 per cent of respondents, while the importance of the experience was highlighted, difficulties in handling the language and tools and expressions of a desire to give up, were present. We conclude that the virtual environment and Internet use can promote knowledge of new codes, symbols, and a specific language, and that this experience impacts on the psychological state of the elderly, changing mood states from negative to positive. © 2010 Taylor & Francis Group, LLC.
Keywords: Elderly; Internet; Leisure